Phase Ib/II study on the safety, tolerability, and preliminary efficacy of pegylated irinotecan (JK1201I) as second‐line monotherapy for patients with small‐cell lung cancer - Jieran Long; Xuefei Li; Lin Wu; Guohua Yu; Aimin Zang; Yanqiu Zhao; Jinsheng Shi; Ligong Nie; Xuan Zhao; Jian Fang (Cancer Medicine)
Abstract Purpose To evaluate the safety, tolerability, and preliminary efficacy of multiple doses of pegylated irinotecan (JK1201I) as a second‐line monotherapy for treating small‐cell lung cancer (SCLC) patients. Methods According to the “3 + 3” dose‐escalation principle, patients received intravenous JK1201I at 180 or 220 mg/m2 once every 3 weeks for four cycles. Progression‐free survival (PFS), overall survival (OS), median progression‐free survival (mPFS), and median overall survival (mOS) were evaluated. The Kaplan–Meier method was used to analyze PFS and overall OS. Brookmeyer and Crowley's method was used for mPFS and mOS. Results This study included 29 patients with stage III–IV SCLC (stage IIIa, n = 1; stage IIIb, n = 1; and stage IV, n = 27). Of these, 26 patients were enrolled in the 180 mg/m2 dose group, and 3 patients were enrolled in the 220 mg/m2 dose group. No dose‐limiting toxicity (DLT) was noted during the first 28 days of treatment. Grade 3 or higher adverse events were recorded in the 180 mg/m2 group, including diarrhea (11.5%, 3/26), neutropenia (7.7%, 2/26), and leukopenia (7.7%, 2/26). In the 220 mg/m2 group, one patient (33.3%, 1/3) experienced neutropenia or leukopenia. In the 180 mg/m2 group, 38.5% (10/26) of patients achieved an objective response rate (ORR), with a disease control rate (DCR) of 73.1% (19/26). The mPFS and mOS were 3.4 and 12.1 months, respectively. In the 220 mg/m2 group, one patient had stable disease, and one had progressive disease (PD). The ORR, DCR, mPFS, and mOS were 0% (0/3) and 33.3% (1/3), 2.7 months and 2.7 months, respectively. Conclusion JK1201I exhibits promising efficacy and relatively low toxicities as a second‐line monotherapy for SCLC, warranting further large‐scale clinical studies to evaluate its efficacy in greater detail.